The impact of the COVID-19 outbreak on Chinese-listed tourism stocks - Wenmin Wu; Chien-Chiang Lee; Wenwu Xing; Shan-Ju Ho (Financial Innovation, 2021)
This research explored the effects of the coronavirus disease (COVID-19) outbreak on stock price movements of China's tourism industry by using an event study method. The results showed that the crisis negatively impacted tourism sector stocks. Further quantile regression analyses supported the non-linear relationship between the government's responses and stock returns. The results present that the resurgence of the virus in Beijing did bring about a short-term negative impact on the tourism industry. The empirical results can be used for future researchers to conduct a comparative study of cultural differences concerning government responses to the COVID-19.
Keywords: G14; L83; 650; China; COVID-19; Event study method; Stock market; Tourism